Analisis Kinerja Keuangan pada Pemerintah Kota Medan - Dola Malau; Anggiat Situngkir (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study aims to analyze the financial performance of the Medan City Government based on six key indicators: (1) growth ratio, (2) degree of fiscal decentralization ratio, (3) regional financial dependency ratio, (4) regional financial independence ratio, (5) regional original revenue (PAD) effectiveness ratio, and (6) regional financial efficiency ratio. The research employs a quantitative descriptive method using secondary data obtained from the Medan City Government’s budget realization reports over the study period. The analysis results indicate that the financial performance of the Medan City Government shows fluctuations across several aspects. The growth ratio reveals an unstable trend, indicating inconsistency in the increase of revenue and expenditure. The degree of fiscal decentralization ratio is 36.66%, suggesting a moderate contribution of PAD to total regional income. The regional financial dependency ratio stands at 61.64%, while the financial independence ratio reaches 59.54%. The PAD effectiveness ratio of 81.36% reflects fairly effective revenue management, and the financial efficiency ratio of 98.44% indicates that financial management has been carried out efficiently. Overall, these findings demonstrate that while Medan City’s financial performance is relatively sound, there remains room for improving fiscal independence and stability.